ESTOQUE DE CARBONO DO SOLO E EVOLUÇÃO DE DIÓXIDO DE CARBONO EM LABORATÓRIO SOB DIFERENTES SISTEMAS DE MANEJO - Dos Santos, Thais; Rosset, Jean; Faria, Elias; Bispo, Luan; Marra, Leandro; Castilho, Selene (ANAIS DO ENIC, 2018)
-